ANTARA EFISIENSI DAN KETERGANTUNGAN: PERAN AI LITERACY DALAM MEMODERASI HUBUNGAN PENGGUNAAN ARTIFICIAL INTELLIGENCE DENGAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PADA MATA KULIAH PERENCANAAN PEMBELAJARAN - Risma Handayani; Yuliani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of Artificial Intelligence (AI) in higher education offers greater efficiency in completing academic tasks, but it also raises concerns about dependency and reduced student engagement in critical thinking processes. This study aims to analyze the use of Artificial Intelligence in Learning Planning courses, identify patterns of efficiency and dependency in AI use, and examine the role of AI Literacy in relation to students’ critical thinking skills. The study employed a quantitative approach with an explanatory survey design. Data were collected through questionnaires measuring AI use and AI Literacy, as well as case-based tests measuring students’ critical thinking skills. The data were analyzed using descriptive statistics and moderation regression to examine the relationship between AI use and critical thinking and the role of AI Literacy in this relationship. The findings indicate that students use AI to generate ideas, understand learning materials, identify alternative learning strategies, and assist in developing learning plans, thereby improving academic efficiency. However, a tendency toward AI dependency was also identified, particularly when students experienced difficulties completing tasks without AI assistance. At the same time, students demonstrated awareness of the need to verify AI-generated information, compare AI outputs with academic sources, and use AI as a supporting tool rather than a substitute for their own thinking. These findings suggest that AI does not automatically weaken students’ critical thinking skills; rather, its impact is influenced by the quality of AI Literacy and patterns of AI use. Strengthening AI Literacy is therefore essential to ensure that AI supports, rather than replaces, students’ critical thinking processes.